Pengaruh Promosi Kesehatan Melalui Media Video Terhadap Pengetahuan Dan Sikap Kader Dalam Pencegahan Stunting - Farida Hidayati; Fairus Prihatin Idris; Septiyanti (Window of Public Health Journal, 2025)
Stunting is a chronic nutritional problem caused by a long-term lack of nutritional intake, resulting in impaired growth in children. The prevalence of stunting in South Sulawesi Province was 151,398 children suffering from stunting or growth failure in 2021. The most fundamental problem in integrated health service posts (Posyandu) is the low level of knowledge of cadres, both academically and technically. Therefore, to provide optimal services, adjustments to the knowledge and skills of Posyandu cadres are necessary. This study aims to determine the effect of health promotion through video media on the knowledge and attitudes of cadres in the Barombong Community Health Center (Puskesmas) work area regarding the prevention of stunting. This type of research is quantitative. The design used in this study is quasi-experimental. The study population was 65 people. The sample in this study was 65 respondents. The instrument used was a questionnaire. The results of the study obtained a p-value of 0.000 <0.05, which means there is an influence of health promotion through video media on the knowledge of cadres in preventing stunting at the Barombong Health Center, a p-value of 0.000 <0.05, which means there is an influence of health promotion through video media on the attitudes of cadres in preventing stunting in the Barombong Health Center work area. This study concludes that the variables of knowledge and attitude influence health promotion through video media in the Barombong Health Center Work Area.